Decoding the Future of Exoplanets: Asteroseismic Confirmation of Subgiant and Red Giant Hosts - Wen-Xu Lin; Sheng-Bang Qian; Li-Ying Zhu; Wen-Ping Liao; Fu-Xing Li; Xiang-Dong Shi; Lin-Jia Li; Er-Gang Zhao (The Astrophysical Journal, 2024)
Asteroseismology has emerged as a powerful tool to unravel the intricate relationships between evolved stars and their planetary systems. In this study, we leverage this technique to investigate the evolutionary stages of five exoplanet host stars, each exhibiting solar-like oscillations. Building on our previous work that identified two host stars as red clump and red giant branch (RGB) stars, this study focuses on a new and broader sample. By precisely measuring asteroseismic parameters such as the period spacing of dipole gravity modes (ΔΠ _1 ), we provide definitive confirmation of these stars’ evolutionary states as subgiants or RGB stars. These results are not only crucial for understanding the internal structures of evolved stars but also for predicting the eventual fate of their planetary companions, which may face engulfment as their host stars expand. This research highlights the profound role of asteroseismology in advancing our knowledge of planetary system evolution and opens new pathways for exploring how stellar evolution impacts planetary survival. Our findings set the stage for future studies on the dynamic fates of exoplanets, providing key insights into the intricate processes of stellar and planetary evolution.